Preparation and characterization of thermally stable ABS/HDPE blend for fused filament fabrication. Issue 2 (25th January 2020) - Harris, Muhammad; Potgieter, Johan; Ray, Sudip; Archer, Richard; Arif, Khalid Mahmood
ABSTRACT: Acrylonitrile butadiene styrene (ABS) is a well-known material used in fused filament fabrication (FFF) for industrial and research applications. However, it has poor thermal stability due to the thermo-oxidative degradation of butadiene monomers. This makes ABS unsuitable for high-temperature structural applications. This research reports a novel FFF blend of ABS with high-density polyethylene (HDPE) in the presence of polyethylene graft maleic anhydride (PE-g-MAH) to improve the thermal stability. A 3 3 full factorial ANOVA analysis is used to analyze the tensile, flexural, and compressive strength of the blend. The novel FFF blend reveals one of the highest mechanical properties in its class in FFF. The thermal stability is significantly enhanced due to the chemical grafting. The results are discussed with the help of Fourier transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), and scanning electron microscopy.